INFORMATION SERVICES THROUGH AUDIO-VISUAL MEDIA THE DANGERS OF GADGET ADDICTION IN EARLY CHILDHOOD - A. Taufiq Hidayat; Ibnu Anshori; Dwi Tjahjono; Mahyadi Mahyadi; Rosi Irianti (EDUCATUM: Scientific Journal of Education, 2024)
Understanding the dangers of gadget use is an understanding that discusses what is meant by gadgets, as well as the impacts caused by gadgets if they are played with for too long. However, in reality, what often happens is that there are still parents who do not understand the dangers of gadget use in early childhood. So it is necessary to make efforts to improve parents' understanding of the dangers of gadget use in early childhood by providing information services through audio-visual media. The purpose of this study was to determine whether information services using audio-visual media have an effect on improving understanding of the dangers of gadget use in parents of students. The research method used is a qualitative research method with a phenomenological research type. The sample or research informants were 5 parents of students at Hidayatut Tholibin Kindergarten, Bojonegoro. Meanwhile, the data collection techniques used in this study were questionnaires, interviews, observations and documentation. Based on the results of interviews before and after being given information services, it was concluded that all informants understood the dangers of gadget use after providing information services through audio-visual media and applying them to students. So it can be concluded that providing information services through audio-visual media has an effect on increasing the understanding of the dangers of gadget use among parents of students at Hidayatut Tholibin Kindergarten, Bojonegoro